Learning Programming Technique through Visual Programming Application as Learning Media with Fuzzy Rating - Buditjahjanto, I.G.P Asto; Nurlaela, Luthfiyah; Ekohariadi; Riduwan, Mochamad (International journal of information and communication technology education, 2017)
Programming technique is one of the subjects at Vocational High School in Indonesia. This subject contains theory and application of programming utilizing Visual Programming. Students experience some difficulties to learn textual learning. Therefore, it is necessary to develop media as a tool to transfer learning materials. The objectives of this study are to determine the feasibility of learning media based on Visual Programming and to investigate the response of students who utilize the learning media. Learning media is firstly validated by experts before it is applied to students. This research implemented rating validation with fuzzy rating based on fuzzy inference system. Fuzzy benefits in translating a crisp form into the preference of linguistic variable form and reprocess into a crisp form as a value decision. The results revealed that fuzzy rating can be implemented to measure the feasibility of learning media and students' responses to the use of learning media.